Internet connectivity disruption in India (India) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in India. Data sourced from IODA.
Network Disruption Incident ID: IN-2026-0159. Severity: critical. Confidence: 67%